Answer:
![g(x)=(x-3)^2-6](https://img.qammunity.org/2020/formulas/mathematics/middle-school/sh8zrnvwcjp5wwwu5fip1b9od6kphd9g2y.png)
Explanation:
we have
The parent function is
-----> The vertex is the point (0,0)
The function g(x) has a vertex at (3,-6)
so
The rule of the translation of f(x) to g(x) is
(x,y) ------> (x+3, y-6)
That means ----> The translation is 3 units at right and 6 units down
therefore
The equation of the function g(x) is
![g(x)=(x-3)^2-6](https://img.qammunity.org/2020/formulas/mathematics/middle-school/sh8zrnvwcjp5wwwu5fip1b9od6kphd9g2y.png)